2011
DOI: 10.1016/j.micpath.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Features of sepsis caused by pulmonary infection with Francisella tularensis Type A strain

Abstract: The virulence mechanisms of Francisella tularensis, the causative agent of severe pneumonia in humans and a CDC category A bioterrorism agent, are not fully defined. As sepsis is the leading cause of mortality associated with respiratory infections, we determined whether, in the absence of any known bacterial toxins, a deregulated host response resulting in sepsis syndrome is associated with lethality of respiratory infection with the virulent human Type A strain SchuS4 of F. tularensis. The C57BL/6 mice infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 49 publications
5
64
0
6
Order By: Relevance
“…A more recent study using a higher aerosol exposure dose demonstrated many similarities in the natural history of pneumonic tularemia in mice and F344 rats infected with aerosolized F. tularensis subspecies tularensis, including the development of inflammation in the lungs, liver, and spleen with severe sepsis and coagulopathy, and high terminal bacterial burdens in these organs and blood at the time of death, 4 to 5 days after infection. 52 The most prominent difference between F344 rats and mice is the susceptibility of the latter to all F. tularensis subspecies, including subspecies novicida and LVS. 24 In this regard, F344 rats more …”
Section: F344 Rat Model Of Inhalational Tularemiamentioning
confidence: 99%
“…A more recent study using a higher aerosol exposure dose demonstrated many similarities in the natural history of pneumonic tularemia in mice and F344 rats infected with aerosolized F. tularensis subspecies tularensis, including the development of inflammation in the lungs, liver, and spleen with severe sepsis and coagulopathy, and high terminal bacterial burdens in these organs and blood at the time of death, 4 to 5 days after infection. 52 The most prominent difference between F344 rats and mice is the susceptibility of the latter to all F. tularensis subspecies, including subspecies novicida and LVS. 24 In this regard, F344 rats more …”
Section: F344 Rat Model Of Inhalational Tularemiamentioning
confidence: 99%
“…It has been suggested that alveolar phagocytes are therefore detrimental to the host during respiratory infection, and a 2005 study reported that depletion of alveolar phagocytes following high challenge doses of LVS resulted in a modestly delayed time to death (7). The course of disease is characterized by a delayed immune response, followed by systemic dissemination and sepsis (8)(9)(10). Consequently, the prevailing opinion is that F. tularensis evades destruction by innate immunity and subverts myeloid cells, particularly macrophages, for its own benefit.…”
mentioning
confidence: 99%
“…The role of IL-6 in immunity to F. tularensis, however, is not yet well defined. Several reports have shown that IL-6 is induced during primary infection of mice with either the virulent strain of F. tularensis SchuS4 or the attenuated LVS (22)(23)(24)(25)(26). In contrast to a potential role for prediction of vaccine-induced protection, IL-6 has also been suggested as a predictor of mortality in BALB/c mice infected intranasally with a dose of LVS that approximated the expected LD 50 (27).…”
mentioning
confidence: 99%